ANALISIS PENDAPATAN USAHA ART SHOP DI KAWASAN SEMINYAK KABUPATEN BADUNG - Devi, Ni Kadek Lidya Paramita Rustiana; Mustika, Made Dwi Setyadhi (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2023)
Bali Province is a rich tourist destination with diverse attractions. One of the well-known regions for tourism in Bali is Badung Regency. The Seminyak area in Badung Regency has experienced rapid development in the tourism and trade sectors. One indicator of this is the increasing number of art shops in the Basangkaja Traditional Village area, which is frequented by tourists. This study aims to analyze the influence of capital, labor, and product variation on the implementation of technology in art shop businesses in the Seminyak area of Badung Regency, and to evaluate the impact of capital, labor, and product variation on the income of art shop businesses through technology implementation. The research sample consists of 99 art shop owners in the Seminyak area of Badung Regency, selected using nonprobability sampling method. Data collection was conducted through observation and structured interviews. Data analysis employed descriptive analysis, path analysis, and Sobel test. The findings confirm the theory that capital, labor, product variation, and technology have an influence on the income of art shop businesses. keyword : capital, labor, product variety, technology and income.